Efficacy and safety of bridging thrombolysis initiated before transfer in a drip-and-ship stroke service - Purrucker, Jan; Heyse, Miriam; Nagel, Simon; Gumbinger, Christoph; Seker, Fatih; Möhlenbruch, Markus Alfred; Ringleb, Peter A. (Stroke and vascular neurology, 2021)
Objective Data regarding the efficacy and safety of bridging thrombolysis (BT) initiated before transfer for evaluation of endovascular therapy is heterogeneous. We, therefore, analyse efficacy and safety of BT in patients treated within a drip-and-ship stroke service. - Methods Consecutive adult patients suffering from acute ischaemic stroke and large-vessel occlusions (LVO) transferred to our comprehensive stroke centre for evaluation of endovascular therapy in 2017-2020 were identified from a local prospective stroke database and categorised according to BT and no-BT. BT was defined as intravenous thrombolysis initiated before transfer. LVO was assessed before and after transfer. Functional outcome before stroke and at 3 months using the modified Rankin scale (mRS) was determined. Excellent outcome was defined as mRS 0-1 or return to prestroke mRS. For safety analysis, intracranial haemorrhages and mortality at 3 months were analysed. Main analysis was limited to patients with anterior circulation stroke. - Results Of N=714 patients, n=394 (55.2%) received BT. More patients in the BT group with documented LVO before transfer recanalised without endovascular therapy (n=46, 11.7%) than patients who did not receive BT before transfer (n=4, 1.3%, p<0.001). In multivariate analysis, BT was the strongest independent predictor of early recanalisation (adjusted OR 10.9, 95% CI 3.8 to 31.1, p<0.001). BT tended to be an independent predictor of an excellent outcome at 3 months (adjusted OR 1.38, 95% CI 0.97 to 1.96, p=0.077). There were no differences in safety between the BT and no-BT groups. - Conclusions BT initiated before transfer was a strong independent predictor of early recanalisation.
First published July 26, 2021
Gesehen am 12.08.2021